Causes Of Conflict In Urban Families: A Sociological Study Of Delhi NCR (Journal of Namibian Studies : History Politics Culture, 2023)
In our society, the family has a very central position. When individuals live in a family, interaction among them is inevitable. That is why conflict is very natural because each individual has their percipience and opinions on various points. Therefore, the main goal of this study is to recognize the root causes of family conflict, especially in urban areas of Delhi NCR region, and find ways to resolve it. The study has followed the quantitative research method and used both primary and secondary sources.Moreover, the questionnaire was filled out and telephonic for collecting primary data. A few personal interviews were done with 50 families (100 respondents of only 20 years to 70 years old individuals) of the region. The study recorded 26 responses for ancestral property conflict and 16 for family business conflict. Moreover, the study received 29 responses agreeing that as women have started going outside for earnings, this causes conflict in their families. Furthermore, the study recorded 12 and 9 responses for household work distribution and ideological differences, respectively, causing family conflict. Besides, intriguingly, the study also found that though most families are involved in one or other form of family conflict, they are always ready to help their family members in case of emergency. Additionally, the study found that avoiding anger, becoming empathetic, cooperating with family members, initiating positive communication, staying calm, etc., can resolve family conflicts.